Analisis potensi kecelakaan kerja di pabrik peralatan pertanian dengan hazard identification risk assesment and risk control (HIRARC) - Wahyu Jati Pamungkas; Risma Fitriani (Journal Industrial Servicess, 2022)
CV. Jasa Bhakti is a company producing agricultural equipment and automotive repair services. Employees who works in the production floor often ignore their own safety by not wearing shoes, glasses, masks, and other personal protective equipment so that they are vulnerable to accidents. The purpose of this study is to identify efforts of company to prevent work accidents. The method in this research is the hazard identification risk assessment and risk control (HIRARC). The data used in the form of historical data on the employees was obtained through observation, interviews, and documentation. The results obtained in this study are known to have 7 machine work processes, namely turning, welding, grinding, boring, carbide welding, scrap, and cutting. In this work, there are 27 hazards with hazard classes of 4 extremes, 4 high, 7 medium, and 12 low. The identification results indicate that the safety management system in the company is not good. Control measures that can be taken is in the form of making Standard Operating Procedures, procuring HSE division, engineering such as designing workplaces to prevent accidents, and education and advice to use personal protective equipment (PPE). This research can be applied to other industries.